Perineural invasion as a predictor of local recurrence in cats with squamous cell carcinoma treated with electrochemotherapy - dos Santos, Francielle Fernanda Quirino; Linhares, Laís Calazans Menescal; Rocha, Michelle do Carmo Pereira; de Oliveira, Krishna Duro; Rangel, Marcelo Monte Mor; de Nardi, Andrigo Barboza (Frontiers in Veterinary Science, 2024)
Introduction: Squamous cell carcinoma (SCC) is a malignant neoplasm that accounts for approximately 15-25% and 70-80% of all feline cutaneous and oral tumors, respectively. Similar to that in humans, feline SCC can be highly invasive locally; however, its metastasis rate is low. Thus, effective local treatment may be curative for most patients, and includes surgery, electrochemotherapy (ECT), cryosurgery, or a combination of these. However, this neoplasia can manifest more aggressively in some patients, leading to higher recurrence rates. In humans, perineural invasion (PNI) has been described as a relevant tumor dissemination pathway associated with high-risk CCESCC, resulting in higher recurrence rates, resistance to local treatments, and short survival. However, PNI and its prognostic value have not been described in feline SCC. This study aimed to evaluate the PNI in a feline population with SCC treated with ECT and correlate its presence with the occurrence of local recurrence and other clinical variables. Methods: Twenty-four cats histopathologically diagnosed with SCC between 2013 and 2021 were retrospectively selected from the medical records of the Oncological Center Vet Cancer (São Paulo, SP, Brazil). The inclusion criteria were ECT as the sole therapy, histopathological evaluation of PNI, and absence of distant metastatic disease. Results: The complete response rate was 96% (23/24), and PNI was identified in 33% of the cats (8/24, PNI-positive group), whereas 67% were free of this invasion (16/24, PNI-negative group). All PNI-positive cats developed local recurrence, whereas only five PNI-negative cats experienced recurrence. Discussion: The results of this study are preliminary but promising. The data obtained are the first regarding PNI occurrence in feline SCC and pave the way for further studies, mainly to correlate the PNI with survival data and better define its prognostic value.